Application of Deuterium and Oxygen-18 to Trace Leachate Movement in Bantar Gebang Sanitary Landfill - E.R. Pujiindiyati (PPIKSN-BATAN, 2011)
Bantar Gebang landfill was constructed in 1986 with total area of 108 ha and approximately 6000 ton/day solid waste is disposed to this landfill. Mostly, the people living surrounding landfill get afraid of impact of the hazardous chemicals produced by waste disposal to their health. The purpose of this investigation was to study the migration of leachate to Cibitung River water and shallow groundwaters near to the river. It is possible to be done because chemical contents and isotopic characteristics of municipal landfill leachate are unique, relative to aqueous media in the most natural environments. Laser absorption method developed by the LGR (Los Gatos Research) was used to measure absolute abundances of 2HHO, HH18O and HHO in a number of water samples. In-situ measurements were also conducted as an additional parameter besides their isotopes. The δ2H of the H2O in landfill leachate was significantly enriched, with values of - 22.6 ‰ to + 4.3 ‰. This deuterium enrichment was undoubtedly due to the extensive production of microbial methane within the limited reservoir of the landfill. However, the enriched deuterium value in leachate was not detected in the river which still had depleted values. It was probably caused by the amount of natural water in the river was comparatively large, with respect to limited leachate discarded to the river. The electrical conductivity of the leachate was higher (3200 to 7600 μS) and the decreasing values were still monitored in the river to approximately 12 km after streaming the landfills. The effect of the high electrical conductivity and enriched deuterium of leachate was not clearly indicated in the groundwater samples which still represented the local precipitation recharge, except a monitoring well located in Bantar Gebang landfill area which has an indication of leachate contamination. Received: 20 November 2010; Revised: 15 June 2011; Accepted: 25 July 2011